ИНТЕРФЕРЕНЦИЈА ВО ИЗРАЗУВАЊЕТО НА ПОЛОТ И НА ГРАМАТИЧКИОТ РОД ВО НОВИНАРСКИТЕ ТЕКСТОВИ НА ИНТЕРНЕТ И ВО ДРУГИТЕ ПИШАНИ МЕДИУМИ (Philological Studies, 2019)
The main aim of this paper is to show the difficulties in understanding the meanings of utterances when there is interference between sex and grammatical gender. For this purpose we used examples from newspaper articles taken from the Internet, which abounds in this kind of documents.